Photoaffinity labeling of the multidrug-resistance-related P-glycoprotein with photoactive analogs of verapamil. - Safa, A R (1988)
Verapamil, a phenylalkylamine calcium channel blocker, has been shown to reverse multidrug resistance in tumor cells, possibly by increasing drug retention through interaction with an outward drug transporter of the resistant cells. In this study two photoactive radioactive analogs of verapamil, N-(p-azido[3,5-3H]benzoyl)aminomethyl verapamil and N-(p-azido[3-125I]salicyl)aminomethyl verapamil, were synthesized and used to identify the possible biochemical target(s) for verapamil in multidrug-resistant DC-3F/VCRd-5L Chinese hamster lung cells selected for resistance to vincristine. The results show that a specifically labeled 150- to 180-kDa membrane protein in resistant cells was immunoprecipitated with a monoclonal antibody specific for P-glycoprotein. Phenylalkylamine binding specificity was established by competitive blocking of specific photolabeling with the nonradioactive photoactive analogs as well as with verapamil. Photoaffinity labeling was also inhibited by 50 microM concentrations of the calcium channel blockers nimodipine, nifedipine, nicardipine, azidopine, bepridil, and diltiazem and partially by prenylamine. Bay K8644, a calcium channel agonist, also inhibited P-glycoprotein photolabeling. Moreover, P-glycoprotein labeling was inhibited in a dose-dependent manner by vinblastine with half-maximal inhibition at 0.2 microM compared to that by verapamil at 8 microM. Photolabeling was also partially inhibited by two of the drugs to which these cells are cross-resistant, doxorubicin and actinomycin D, at 100 microM, but not by colchicine. These data provide direct evidence that P-glycoprotein has broad drug recognition capacity and that it serves as a molecular target for calcium channel blocker action in reversing multidrug resistance.